Analisis Kepuasan Pengguna Mobile Banking Danamon Menggunakan Metode Technology Acceptence Model (TAM) - Randa, Novia; Syahra, Yohanni (Jurnal Sains, Teknologi & Komputer, 2025)
With the advancement of digital technology, the banking sector—including PT Bank Danamon Indonesia—has begun offering mobile banking services such as D-Bank PRO.This study investigates three key variables that influence user satisfaction with Danamon’s mobile banking services: Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Attitude Toward Use. Several obstacles to application usage were identified, including the absence of a notification system, uncertainty regarding long-term benefits, and malfunctioning features. A quantitative research method was employed, utilizing an online survey distributed to one hundred D-Bank PRO users. Furthermore, data analysis was conducted using the SPSS software. The results indicate that all TAM variables significantly affect user satisfaction, with PEOU emerging as the most dominant factor. These findings provide strategic guidance for enhancing the quality and usability of mobile banking services to achieve higher user satisfaction.